The Proposed Research Framework of Organizational Agility - Taufan Umbara; Astadi Pangarso; Retno Setyorini (Journal of Economics, Business, and Accountancy Ventura, 2023)
Organizational agility is the ability of an organization to respond to organizational dynamics. This paper applies a systematic literature review (SLR) based on the PRISMA protocol and theory-context-characteristic-methodology (TCCM) analysis to find research gaps and construct a research framework concerning organizational agility. By reviewing previous research publications with the following criteria: quantitative research documents indexed by Scopus as journals; in the subject area of Business, Management, and Accounting; written across 2005‒2020 in English and downloadable in full text; and empirical studies using structural equation modeling in data processing presents several research gaps. A research framework proposal is compiled concerning these research gaps, comprising 14 propositions. The proposed research framework of organizational agility is expected to provide the basis for future empirical studies.